The greenback : paper money and American culture - Tschachler, Heinz (Jefferson, N.C. : McFarland, 2010)
"This text explores the social, cultural and historical contexts of paper money. Predicated on the assumption that paper bills speak to us through the use of symbols--letters, verbal and visual elements, as well as symbols of civic values--this book examines what has been conveyed to Americans via their currency from Colonial times through the present day"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Paper money -- United States -- History; Dollar, American -- History